A Needs Analysis of Students’ Vocabulary Learning as a Foundation for Web-Based EFL Material Design - Nurismi, Nurismi; Aini, A. Nur Inayatul; Hidayanto Pancoro Setyo Putro, Nur; Rahmawati, Sholihatul Isnaini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study aims to investigate secondary school students’ vocabulary learning needs in web-based English as a Foreign Language (EFL) contexts by examining their learning goals, perceived vocabulary proficiency, learning preferences, learning challenges, and the use of web-based learning platforms. This study employed a descriptive needs analysis involving 63 Grade X students at a public senior high school in Indonesia. Data were collected through questionnaires, semi-structured interviews, and classroom observations. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically to support and enrich the quantitative findings. The findings indicate that most students perceive their vocabulary proficiency to be at the beginner level and demonstrate a strong need for contextualized vocabulary learning supported by multimedia features. Students also reported, difficulties related to limited vocabulary mastery, low vocabulary retention, and insufficient exposure to English outside the classroom. Furthermore, although students viewed web-based learning platform as beneficial for enhancing engagement, they emphasized the need for clear instructional guidance to maximize their learning effectiveness. Unlike previous studies that separately examined vocabulary learning or web-based technology, this study integrates students’ vocabulary needs, perceived proficiency, learning preference, learning challenges, and web-based learning expectations into a single comprehensive needs analysis. This integrated profile provides an empirical basis for designing learner-centered web-based vocabulary materials specifically for Indonesian secondary school EFL learners.